Cecil essentials of medicine - Andreoli, Thomas E (W.B. Saunders, 1997)
B. Saunders. University of Arkansas, Little Rock. Synopsis of the core elements of the 20th edition of the parent textbook, c1996, by Bennett. Concise format. Previous edition: c1993. By a Brandon/Hill author. 41 U.S. contributors. Softcover. DNLM: Internal medicine.
Keywords: lékařství; Medicine